Comparisons of health-related factors in children with attention-deficit/hyperactivity disorder with and without sleep problems following a weighted blanket sleep intervention - Malmborg, Julia S.; Tuvesson, Josefine; Larsson, Ingrid; Svedberg, Petra; Nygren, Jens; Jarbin, Håkan; Lindholm, Annelie (BMC Pediatrics, 2025)
Background: Adequate sleep is crucial for children’s health, especially for children with ADHD and concurrent sleep problems. There is a need for more studies focusing on sleep problems in children with ADHD as these problems may exacerbate ADHD symptoms and vice versa, impacting negatively on everyday life. The aim of this study was to investigate the differences in health-related factors between children with ADHD without clinically relevant sleep problems and those with clinically relevant sleep problems after a sleep intervention. Methods: This cross-sectional study involved 83 children diagnosed with ADHD and sleep problems, 46 boys and 37 girls; aged 6–14 years, divided into two groups after a sleep intervention according to the parent-reported Children’s Sleep Habits Questionnaire (CSHQ) and a cut-off for clinically relevant sleep problems. Data from a 16-week follow-up of the sleep intervention were analysed in terms of the following health-related measures: The Insomnia Severity Index (ISI), The short form of State-Trait Anxiety Inventory (Short-STAI), The Child Outcome Rating Scale (CORS), The EQ-5D-Y-3L (child-reported), and The Swanson, Nolan, and Pelham Rating Scale (SNAP-IV) (parent-reported). The Mann-Whitney u-test, Independent samples t-test, and Chi-square/Fisher’s exact test were used for the analysis. Results: Forty-two of the 83 children (50.6%) were grouped as having clinically relevant sleep problems and 41 (49.4%) as being without the same. The results indicated that the group without clinically relevant sleep problems reported less insomnia (ISI, total score p = 0.011), less tension in the anxiety scale (Short-STAI, tense p = 0.047), and their parents reported less ADHD symptoms (SNAP-IV, total score for attention deficit, p < 0.001). No group differences were observed for life functioning (CORS) or health-related quality of life (EQ-5D-Y-3 L). Conclusions: This study showed that children with ADHD without parent-reported clinically relevant sleep problems had fewer health-related issues after a sleep intervention, including self-reported insomnia, tension, and parent-reported ADHD symptoms, compared to children with clinically relevant sleep problems. Longitudinal studies are necessary to fully comprehend the long-term impact of sleep problems and various health-related factors in this cohort.
Keywords: Attention-deficit/hyperactivity disorder; Children; Health; Sleep